2021
DOI: 10.1029/2021jf006163
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and Geologic Controls on Frost Cracking in Alpine Rockwalls

Abstract:  Temperature loggers provide rock temperature data that incorporates topographic effects on insolation and insulation. Sensitivity tests on frost cracking models showed differences of frost magnitude while frost cracking depth patterns were consistent. Thermo-mechanical models incorporating rock strength and hydraulic properties produced more realistic altitudinal frost cracking patterns.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 118 publications
(346 reference statements)
2
32
0
Order By: Relevance
“…Grosse Grabe North Pillar, as indicated by the modelling results of rock walls at similar elevation and exposition (Draebing & Mayer, 2021). This way, frost weathering is preparing rock wall instabilities, subsequently triggered by processes in summer such as thermal stresses described above.…”
Section: Conditions Leading To Rock Wall Destabilizationmentioning
confidence: 67%
See 1 more Smart Citation
“…Grosse Grabe North Pillar, as indicated by the modelling results of rock walls at similar elevation and exposition (Draebing & Mayer, 2021). This way, frost weathering is preparing rock wall instabilities, subsequently triggered by processes in summer such as thermal stresses described above.…”
Section: Conditions Leading To Rock Wall Destabilizationmentioning
confidence: 67%
“…The cumulative and repetitive nature of thermally induced failure mechanisms is considered an important preparatory factor for rockfall in fractured rock masses exposed to large temperature oscillations (Bakun‐Mazor et al, 2020; Collins & Stock, 2016; Draebing et al, 2017; Gunzburger et al, 2005). Although no in‐situ rock temperatures were measured at the south‐facing rock wall of Grosse Grabe, similar south‐exposed rock walls yield a daily temperature variation of up to 16.5°C compared to only 4°C for north‐facing rock walls as a result of solar radiation differences (Draebing & Mayer, 2021). While daily temperature changes only penetrate down to shallow depths (≤0.4 m) (Gunzburger et al, 2005), seasonal thermal changes can propagate deeper in highly fractured bedrock (up to 100 m) due to air convection (Gischig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of these different mechanisms can be studied. Frost‐weathering sets in when the daily mean air temperature drops below a freezing temperature threshold and snow depth is below a threshold to not insulate the bedrock (e.g., Draebing & Mayer, 2021). Rainfall‐induced landslides happen when daily rainfall exceeds a threshold (e.g., Leonarduzzi et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This will affect especially rockwalls located at lower elevations; therefore, cryogenic processes and triggered rockfall will be shifted to higher elevations. At higher elevations, the climate-change-induced changes in the temperature regime will also affect permafrost rockwalls, decrease rockwall stability (Krautblatter et al, 2013;Draebing et al, 2014) and increase rockfall activity due to increased thawing amplified by temperature extremes (Gruber et al, 2004a;Ravanel et al, 2017). Rockfall should be quantified and linked to climatic drivers to predict the effects of climate change on rockfall more accurately.…”
Section: Altitudinal Effects On Rock and Fracture Kinematics And Implications For Rock Stabilitymentioning
confidence: 99%
“…Current research highlights the role of mechanical weathering (Eppes and Keanini, 2017). Diurnal and seasonal ambient meteorological changes causing cyclic heating and cooling (Gunzburger and Merrien-Soukatchoff, 2011;Collins and Stock, 2016), wet-dry cycles (Zhang et al, 2015), freeze-thaw cycles (Matsuoka, 2001(Matsuoka, , 2008 or active-layer thaw (Draebing et al, 2014(Draebing et al, , 2017a) produce critical and subcritical stresses that propagate micro-fractures (Eppes et al, 2018;Draebing and Krautblatter, 2019). Several studies investigated the influence of thermal changes on rockwalls and demonstrated that sudden erosion by thermal shock (Collins et al, 2018(Collins et al, , 2019 and slow thermally induced propagation of fractures in alpine rockwalls (Hasler et al, 2012;Collins and Stock, 2016;Weber et al, 2017) continuously weakens rock and can trigger rockfall (Ishikawa et al, 2004;Collins and Stock, 2016).…”
Section: Introductionmentioning
confidence: 99%